Porous carbon electrocatalyst with exclusive metal-coordinate active sites for acidic oxygen reduction reaction. (June 2018) - Zhang, Qiao; Wang, Junhu; Yu, Peiwen; Song, Fei; Yin, Xue; Chen, Renjie; Nie, Hailiang; Zhang, Xiaoling; Yang, Wen
Abstract: A porous P-doped M/N/C electrocatalyst with high-surface-area (up to 1312 m 2 g −1 ) was prepared by annealing a mixture of triphenylphosphine, polyaniline, phthalocyanine iron (II), and phthalocyanine cobalt (II). The synthesis involves hard templating with silica nanoparticles, followed by NH3 activation. Along with low metal loading (Fe loading = 0.46 wt. %; Co loading = 0.26 wt. %), the resulting P-doped M/N/C exhibits an excellent ORR activity and durability in acidic media. The half-wave potential difference of the catalyst for ORR is only ∼53 mV negative relative to the benchmarked Pt/C (360 μg Pt) at the same loading. More importantly, transmission electron microscopy, X-ray absorption fine structure spectra, and electrochemical poisoning by SCN − ion suggested that exclusive metal-coordinate catalytic active sites such as Fe-N6 and Co-N4, are involved in ORR. Moreover, as-prepared P-doped M/N/C catalysts with bimetallic catalytic active sites exhibit superior electrochemical performance compared to catalysts with single metal active sites. These results represent an important step towards rational design of high-performance ORR electrocatalysts for polymer exchange membrane fuel cells. Graphical abstract: Image 1